Nanoscale stoichiometric analysis of a high-temperature superconductor by atom probe tomography - Pedrazzini, S; London, A; Gault, B; Saxey, D; Speller, S; Grovenor, C; Danaie, M; Moody, M; Edmondson, P; Bagot, P (Cambridge University Press, 2017)
The functional properties of the high temperature superconductor Y1Ba2Cu3O7- (Y-123) are closely correlated to the exact stoichiometry and oxygen content. Exceeding the critical value of 1 oxygen vacancy for every 5 unit cells ( > 0.2, which translates to a 1.5 at.% deviation from the nominal oxygen stoichiometry of Y7.7Ba15.3Cu23O54-) is sufficient to alter the superconducting properties. Stoichiometry at the nanometre scale, particularly of oxygen and other lighter elements, is extremely difficult to quantify in complex functional ceramics by most currently available analytical techniques. The present study is an analysis and optimisation of the experimental conditions required to quantify the local nano-scale stoichiometry of single crystal yttrium barium copper oxide (YBCO) samples in 3D by Atom Probe Tomography (APT). APT analysis required systematic exploration of a wide range of data acquisition and processing conditions to calibrate the measurements. Laser energy, ion identification and the choice of range widths were all found to influence composition measurements. The final composition obtained from melt-grown crystals with optimised superconducting properties was Y7.9Ba10.4Cu24.4O57.2 at.%.